2019
DOI: 10.4081/mrm.2019.9
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between chest ultrasonography and chest X-ray in patients who have undergone thoracic surgery: preliminary results

Abstract: Background: Chest Ultrasonography (chest US) has shown good sensibility in detecting pneumothorax, pleural effusions and peripheral consolidations and it can be performed bedside. Objectives: The aim of the study was to analyze agreement between chest US and chest X-ray in patients who have undergone thoracic surgery and discuss cases of discordance. Methods: Patients undergoing thoracic surgery were retrospectively selected. Patients underwent routinely Chest X-ray (CXR) during the first 48 h after surgery. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Imaging studies play a pivotal role in the diagnosis and management of pleural disease, this study shows perfect and strong agreement between X-ray, CT and US in evaluation of amount of pleural effusion with moderate agreement between CT and US in evaluating the pattern of effusion even free or loculated with superiority of US which diagnose 40% of the cases in comparison with CT which diagnose 27% so the Chest US can represent the gold-standard technique (9) . This in agreement with Smargiassi et al (10) Who report US inter-rater agreement with Chest X-ray of a fair magnitude, Sobhyet al (11) study the ability to detect pattern of pleural effusion (free or loculated) and revealed that both CT and US were close to each other but with no significant difference.…”
Section: Discussionsupporting
confidence: 84%
“…Imaging studies play a pivotal role in the diagnosis and management of pleural disease, this study shows perfect and strong agreement between X-ray, CT and US in evaluation of amount of pleural effusion with moderate agreement between CT and US in evaluating the pattern of effusion even free or loculated with superiority of US which diagnose 40% of the cases in comparison with CT which diagnose 27% so the Chest US can represent the gold-standard technique (9) . This in agreement with Smargiassi et al (10) Who report US inter-rater agreement with Chest X-ray of a fair magnitude, Sobhyet al (11) study the ability to detect pattern of pleural effusion (free or loculated) and revealed that both CT and US were close to each other but with no significant difference.…”
Section: Discussionsupporting
confidence: 84%
“…Mediastinal pleura, visceral pleura inside fissures, and costal pleura are masked by shoulder blades and ribs, and are thus generally not accessible for US evaluation 245,246 …”
Section: Methodsmentioning
confidence: 99%
“…Currently, the main limit for LUS evaluation is the presence of massive subcutaneous emphysema, infiltration of air in the layers of the chest wall that hampers US penetration 246 …”
Section: Methodsmentioning
confidence: 99%
“…Because the necessity to develop acquisition strategies specifically designed for lung has been highlighted not only by clinicians, but also by researchers with technical backgrounds, the development of quantitative approaches could represent the future of LUS (Demi et al 2014). The evaluation of correlations between anatomical findings observed with standard imaging modalities (e.g., chest x-rays and CT), which are linked to histological observations, and LUS patterns (Soldati et al 2016(Soldati et al , 2017Smargiassi et al 2019Smargiassi et al , 2020a should represent an important starting point for developing ultrasound approaches specifically dedicated to lungs. This comparison could indeed allow researchers to study the link between the air spaces' (alveoli) resizing and spatial reorganization, as caused by different pathologies, and the quantifiable features of LUS artifacts (Soldati et al 2019(Soldati et al , 2020b.…”
Section: Introductionmentioning
confidence: 99%